Effectiveness of Short-Term Heat Acclimation on Intermittent Sprint Performance With Moderately Trained Females Controlling for Menstrual Cycle Phase - Garrett, Andrew T.; Dodd, Edward; Biddlecombe, Victoria; Gleadall-Siddall, Damien; Burke, Rachel; Shaw, Jake; Bray, James; Jones, Huw; Abt, Grant; Gritt, Jarrod (Frontiers in Physiology, 2019)
Introduction: Investigate the effectiveness of short-term heat acclimation (STHA), over 5-days (permissive dehydration), on an intermittent heat stress test (HST) with females. Controlling for menstrual cycle phase. Material and methods: Ten, moderately-trained, females (Mean [SD]; age 22.6 [2.7] y; stature 165.3 [6.2] cm; body mass 61.5 [8.7] kg; 43.9 [8.6] mL.kg-1.min-1) participated. The HST (31.0°C; 50%RH) was 9 x 5min (45-min) of intermittent exercise, based on exercise intensities of female soccer players, using a motorised treadmill and Wattbike. Participants completed HST1 vs HST2 as a control (C) trial. Followed by 90 min, STHA (no fluid intake), for 5 consecutive days (39.5oC; 60%RH), using controlled-hyperthermia ( rectal temperature [Tre] 38.5oC). The HST3 within one week after STHA. The HST2 vs HST3 trials were in the luteal phase, using self-reported menstrual questionnaire and plasma 17β-estradiol. Results: Pre (HST2) vs post (HST3) STHA there was a reduction at 45-min in by 0.20°C (95%CI -0.30 to -0.10°C; d =0.77); (-0.50; -0.90 to -0.10°C; d =0.80); and (-0.25; -0.35 to -0.15°C; d =0.92). Cardiac frequency reduced at 45-min (-8; -16 to -1 b.min-1; d = 1.11) and %PV increased (7.0; -0.4 to 14.5%: d =1.27). Mean power output increased across all nine maximal sprints by 56W (-26 to 139W; d =0.69; n=9). There was limited change (P>0.05) for these measures in HST1 vs HST2 C trial. Discussion: Short-term heat acclimation (5-days) using controlled-hyperthermia, leads to physiological adaptation during intermittent exercise in the heat, in moderately trained females when controlling for menstrual cycle phase.